Instructional Communication Management Strategy in Curriculum Development of Indonesia Higher Education Institutions - Laskmi Dewi; Nanda Khaerunisa Syafitri; Dinn Wahyudin; Deni Darmawan; Yulia Rahmawari (Jurnal Edutech Undiksha, 2024)
Universities need to have an educational focus by using a multicampus system that must be integrated to achieve its goals. Therefore, an instructional communication strategy needs to be implemented to support management in building communication. This study is to analyze instructional communication strategies and lecturer competency management policies that can be understood and implemented in the teacher education curriculum. The method used in this research is a descriptive method with a quantitative approach with data collection techniques through questionnaires regarding the teaching team's instructional communication management. The research results show that the instructional communication strategy by lecturers in the university environment has been implemented very well. Classroom learning activities, including instructional communication planning, selection of learning methods and strategies, selection of material delivery systems, and use of teaching materials, have also been carried out very well. It happens with lecturers' communication skills and support from university leaders. It hopes that the instructional communication strategy in curriculum development for lecturer educational institutions can be further developed with training related to the development of learning activities starting from lesson planning, learning methods, and strategies to aspects of assessment and evaluation.